A mathematical model for sediment yield in agricultural watershed - BABU V; Dr. A. N Remadevi (Guide) (Tavanur 1998 Kelappaji College of Agricultural Engineering and Technology)
A mathematical model for sediment yield in agricultural watershed
A mathematical model for sediment yield in agricultural watershed